A qualitative study on non-adherence to oral hypoglycemic agents in type 2 diabetics - Agarwala, Sourav; Ansari, Md. Asif; Paul, Uttam Kumar; Bandyopadhyay, Arup (International Journal of Advances in Medicine, 2017)
Background: Non-adherence to oral hypoglycaemic agents is both a global and ubiquitous problem during treatment of type 2 diabetes mellitus. This leads to unwanted persistence and aggregation of hyperglycemia as well as many of the complications of diabetes mellitus and even to early death. However, there have been quite a few studies on this issue but different studies have shown different reasons of non-adherence because of this confusion and also because no studies have been done in Bihar and North Bengal, the present authors decided to go for a qualitative study on this issue. Methods: This study was conducted in the medicine OPD of two medical colleges one in Bihar and another in north Bengal. The study method was one of the qualitative descriptive nature in which open interviews are conducted on non-compliant diabetic patients. Audio recording was taken in each case after taking written permission from the patients as well as from the institutional ethical committee. A transcript in English was made manually of each audio recording and then transcript analysis was done using categories and codes. Results: The results showed existence for four broad categories, viz, adverse effect, economic issues, availability and alternative treatment. Each category was divided into several codes like - adverse effects into weakness, hypoglycemia, organ damage, vertigo and fear; economic issues into high cost, low income, lifelong high expenditure and family crisis; availability into total non-availability, local non-availability, travel expenses and problems to buy from distance and brand non-availability; lastly alternative treatment included Ayurveda, Homeopathy and jori-buti. The last two categories, viz, non-availability and alternative therapy are very much unique in our study. Conclusions: It can be concluded that non-adherence is very much a problem in our places as it is in other places, nationally and globally. But it is slightly different here. We must find out solutions for this problem and start interventions immediately.